Influence of Air Pollution and Soil Contamination on the Contents of Polycyclic Aromatic Hydrocarbons (PAHs) in Vegetables Grown in Urban Gardens of Sao Paulo, Brazil - Amato-Lourenco, Luís F.; Saiki, Mitiko; Saldiva, Paulo H. N.; Mauad, Thais (Frontiers in Environmental Science, 2017)
Urban community gardens (UCGs) have become prevalent worldwide and play a significant role in strengthening the sustainability of urban food systems. Although UCGs provide multiple benefits to society, the extent to which vegetables grown in them are contaminated by chemical compounds derived from airborne fallout or soil contamination is unclear. We evaluated the influence of both air pollution and the contamination of garden soil beds on the contents of 16 PAHs in the edible tissues of spinach and collard green. The PAH contents were quantified using gas chromatography-mass spectrometry (GC-MS-EI). The concentrations of PAHs in both the vegetables grown in the vessels and in the soil of the UCGs were <0.1 μg kg−1. The total concentrations of the 16 priority PAHs in the soil beds ranged from 132.94 to 410.50 μg kg−1. These levels were lower than those that have been reported from other urban areas. Principal Component Analysis resulted in two components indicating that traffic-derived emissions are the main sources of PAHs in the soil. The first component represented the compounds with higher molecular weights and had a moderate loading for the fine fraction of the soil (clay) (0.63). The second component showed a high loading for silt (0.97), including those PAHs with lower molecular weights. Our data show that spinach and collard greens do not accumulate significant PAH concentrations on their leaves over 45-day periods, whether they are raised in controlled soil or in local beds.